Multifactor models do not explain deviations from the CAPM - MacKinlay, A.Craig (Journal of Financial Economics, 1995)
A number of studies have presented evidence rejecting the validity of the Sharpe-Lintner capital asset pricing model (CAPM). Possible alternatives include risk-based models, such as multifactor asset pricing models, or nonrisk-based models which address biases in empirical methodology, the existence of market frictions, or the presence of irrational investors. Distinguishing between the alternatives is important for applications such as cost of capital estimation. This paper develops a framework which shows that, ex ante, CAPM deviations due to missing risk factors will be very difficult to detect empirically, whereas deviations resulting from nonrisk-based sources are easily detectable. The results suggest that multifactor pricing models alone do not entirely resolve CAPM deviations.